The viscount who vexed me - London, Julia (London, Julia. Royal match, 2023)
"Next to the Season's newest diamond, Harriet (Hattie) Woodchurch feels like a plain Jane. But that's of no consequence, since Hattie's plan for her future is to earn enough to live far, far away from her embarrassing family. That is until Mateo Vincente, Duke of Santiava and newly minted Viscount Abbott, arrives in London. While the shy European's spoken English is impeccable, his writing is less fluent. The ton is eager to meet the handsome bachelor, and so many invitations flood in that Mateo needs a correspondence secretary. With her perfect penmanship and way with words, Hattie is recommended, and the two bond over books and the ton's eligible ladies. But when Hattie's friend Flora becomes smitten with the viscount, things get complicated. Flora is tongue-tied in his presence. To help, Hattie feeds her information about Mateo's interests. Soon things turn around and Flora appears on track to become his duchess. Yet for Mateo, something's not right. Conversation with Flora isn't as scintillating as it is with Hattie..."--Page [4] of cover.